Segmentation of Entertainment Consumers: An Ecuadorian Experience - Morales Vergara, José; Pérez Gosende, Pablo; Arevalo Avecilla, Danny; Padilla Lozano, Carmen; Albán González, Guilermo (PODIUM, 2017)
This paper is the result of applying post-hoc segmentation procedures to entertainment custorners in Latacunga, in Ecuador. Qualitative exploratory tools such as group focusing and the Delphi mediad were used for identifying and validating the features that costurners value when selecting their entertainment. Multivariate statistical techniques like hierarchical cluster analysis and discriminant analysis were used to prepare this paper. Respondents were classified based on the preferences they showed when selecting their entertainment. This research aims to classify Latacunga entertainment according to the benefits they sought. It was found that there were three well defined customer groups: Sorne customers were very demanding; sorne were conformists and others looked for artistic offers. Quite a few wanted improvernent in customer service.